PSXIII-21 Water consumption evolution during later gestation is associated to the farrowing day. (8th October 2021) - López-Vergé, Sergi; Mainau, Eva; Verdú, Marçal; Gasa, Josep; Castells-Rufas, David; Manteca, Xavi; Castillejos, Lorena
Abstract: The aim of this study was to verify the utility of water consumption as an indicator to early predict the farrowing day. A total of 28 flowmeters (iPERL®) were installed in two farrowing rooms (12 + 16 places) to record every hour the individual water consumption from the entry of the sows (Landrace × Large White) in the farrowing unit until parturition, along 5 consecutive batches (120 sows). Up to 200, 377 records were managed using Python code. Data were analyzed by using the MIXED procedure of SAS. Parity (gilts, G; sows, S), time slot (morning, M: 6-14h; afternoon, A: 14-22h; night, N: 22-6h) and pre-farrowing days (-9 to -1) and farrowing (0) were included as fixed factors and the farrowing crate as a random effect. Water consumption was lower in gilts (G: 6.9 ± 1.12 L/d vs S: 8.5 ± 1.09 L/d; P < .0001). Up to 57.5% of water consumption occurred in the morning (M: 13.1 ± 1.11 L), 31.0% (A: 7.1 ± 1, 11 L) during the afternoon/evening and 11.8% (N: 2.7 ± 1.11 L) at night. From day -9 (4.9 ± 1.29 L) to -3 (9.2 ± 1.17 L), water intake lineally increased (around 0.8 L/d), highlighting the increase in 2 L at day -2 (11.2 ± 1.16 L; P < .0001). This peak could be related to a greater manipulation of the drinker due to nesting behavior. Finally, on day -1 a drastic and significant decrease in intake was observed (7.3 ± 1.16 L; P < .0001), just before the decrease in feed intake on day 0. The results suggest that water intake can be a valid indicator to early predict the day of farrowing, thus allowing foremen to better plan the management routines in the farrowing unit, especially in large sow farms.